Tributación de la iglesia católica y demás cultos en Colombia (2023)
The following review article offers information about the tax management that the Catholic Church and other cults, regarding these obligations, which are present for the other sectors of society in Colombia. The purpose of the article is to make known, why the attempts to tax these groups have been unsuccessful, since despite the debates that took place in the Congress of the Republic so that this sector will enter to participate with the payment of taxes in the Reform Tax was not possible, being seen as an unequal aspect, since the contribution of these is the contribution that all sectors make to improve the living conditions of people, since the collection of these taxes is the main source of income for the State to guarantee goods and services to citizens. The methodology to be developed is the explanation from the norm, of why these groups are are exempt from paying taxes in Colombia and other Latin American countries.